Pengembangan Multimedia Flipbook Interaktif Berbasis Problem Based Learning pada Materi Instalasi Tenaga Listrik - Kadek Aditia; I Putu Suka Arsa; Wayan Mahardika Prasetya Wiratama (Jurnal Pendidikan Teknik Elektro Undiksha, 2026)
This research aims to develop an interactive flipbook multimedia based on Problem Based Learning on Electrical Power Installation materials. Research using the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Validation is carried out by content experts and media experts, and tested to students through small group and large group tests. The research results show a feasibility level of 91,66% from content experts and 96,25% from media experts with a very decent category. The small group test obtained a percentage of 81.86% and the large group test of 83.64% with the very good category. This result shows that PBL-based interactive flipbook multimedia is suitable to be used to support the learning of Electric Power Installation that is more interactive, interesting, and centered on learners.